2014
DOI: 10.1007/s11095-014-1423-2
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Delivery of Fibroblast Growth Factor-9 from Biodegradable Poly(ester amide) Fibers for Building Functional Neovasculature

Abstract: This study supports the premise of controlled delivery of FGF9 from PEA electrospun fibers for potential therapeutic angiogenesis applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Other proteins, such as fibroblast growth factor 9 (FGF9) and vaccination antigens, have also been proven to retain their biological activity in PEA-based carriers (dos Santos et al, 2009;Said et al, 2014). As further proof of CXCL1 activity after release, we observed significant in vivo evidence of microsphere released CXCL1.…”
Section: Discussionsupporting
confidence: 55%
“…Other proteins, such as fibroblast growth factor 9 (FGF9) and vaccination antigens, have also been proven to retain their biological activity in PEA-based carriers (dos Santos et al, 2009;Said et al, 2014). As further proof of CXCL1 activity after release, we observed significant in vivo evidence of microsphere released CXCL1.…”
Section: Discussionsupporting
confidence: 55%
“…Cells on FGF9-supplemented PEA mats showed upregulation of PDGFRβ dependent on the concentration and cell type. 31 With regard to morpholino-2,5-dione polymerization (see section 2), lipasecatalyzed ROP of isoleucine-based 3(S)-sec-butylmorpholine-2,5-dione (BMD) was described to afford poly(BMD), an optically active PEA with specific stereoregularity (dyads) ( Fig. 1B).…”
Section: General Aspects Of Poly(ester Amide) Synthesismentioning
confidence: 99%
“…[11] Using blend and emulsion electrospinning approaches, a differential and sustained release of growth factors from PEA fibres has been achieved. [115,119] Data from ischemic mice limb studies had shown a considerable functional recovery when the growth factors were delivered from a fibrous mat. [118] Non-covalent incorporation of growth factors is another loading strategy that has been used for the regeneration of tissues.…”
Section: Growth Factor Loading Strategies and Release Kineticsmentioning
confidence: 99%